The effect of cryogenic application on surface integrity in manufacturing process: A review - A. Raof, Natasha; A. Ghani, Jaharah; Che Haron, Che Hassan; Syarif, Junaidi (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
The quality of work material’s surfaces after undergone various manufacturing processes is very important in determining the functional performance of a component throughout the services. Application of coolant and lubricant in manufacturing operations such as turning, milling, grinding, rolling, etc. has been proven to improve the surface integrity of the work materials. In this review, application of cryogenic coolant in manufacturing operations was investigated in terms of its effects on surface integrity of the work materials which includes surface finish, microstructural changes, refinement of grain size, formation of white layer, residual stresses of internal subsurface layer, and surface hardness. Cryogenic application is able to reduce the value of surface roughness, allow for more comprehensive martensitic transformation, reduce the grain size, prevent the formation of white layer at the subsurface, reduce the tensile residual stresses and increase compressive stresses area, and finally increase the hardness of the work material. In conclusion, cryogenic application in a lot of manufacturing processes has been determined to be able to enhance and improve the quality of the workpiece surface, consequently, boost the functional performance of the components.